Persepsi Mahasiswa Program Studi Pendidikan Ekonomi Universitas Pendidikan Ganesha Terhadap Profesi Guru - Suparsini, I Gusti Ayu Bintang; Sujana, I Nyoman (Jurnal Pendidikan Ekonomi Undiksha, 2023)
The purpose of the study is to determine the perception of students of the Economic Education Study Program at Ganesha University of Education toward the teacher profession. This research used a descriptive type with a quantitative approach. The population in this study is active students of the Economic Education Study Program at Ganesha University of Education, class of 2018, who have carried out Field Experience Practice activities, totaling 84 students. This research used a sample of 84 students who used the saturation sampling technique. Data collection in this research used questionnaires and documentation. The data analysis technique used is descriptive analysis. The results of the study showed that students’ perceptions in terms of the interest dimension, with a score of 2.976, were included in the good category. Meanwhile, students’ perceptions in terms of the dimension of experience with a score of 5.902 are included in the highly good.